Bringing Managers Back in: Support for Gender-Equality Measures in the Business Sector - Kitterød, Ragni Hege; Teigen, Mari (Nordic Journal of Working Life Studies, 2018)
The progression of gender balance in top positions at big corporations in Nordic countries has not lived up to the expectations. Inspired by studies emphasizing the crucial role of top management in gaining support for gender-equality measures to make changes happen, we set out to investigate what kind of policies top managers in Norway would prioritize to further gender balance in the executive ranks. We found that active recruitment policies receive the strongest support and quota and preferential-treatment policies the least support. We found clear similarities between men and women in the ranking of measures, although women generally indicated stronger support for most measures. We found no differences related to gender composition of the management group, but some differences across company types (subject to CBQ or not) were revealed. Although corporate-board quotas received the least support, there was no indication that these measures were strongly objected.